Encyclopedia of Environmental Microbiology 2003
DOI: 10.1002/0471263397.env316
|View full text |Cite
|
Sign up to set email alerts
|

Methanotrophic Bacteria

Abstract: Classification of Methanotrophs Biochemistry and Molecular Biology of Methanotrophic Bacteria Ecology of Methanotrophic Bacteria Methanotrophs and Biotechnology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 135 publications
2
10
0
Order By: Relevance
“…However, the ratios of 13 C-labeled type II to type I methanotrophs were 20.0 to 101 in the low-pH soils of YX, YT and TY (Table S4). Assuming that one cell contained two copies of pmoA genes (Kolb et al, 2003), type II methanotrophs could reach a cell-specific methane oxidation rate of 0.2-9.6 fmol CH 4 h −1 cell −1 in these three soils (calculated in Table S4), being consistent with previous report of 0.2-15 fmol CH 4 h −1 cell −1 obtained from both pure cultures and complex soils (Hanson and Hanson, 1996). These results thus suggest that aerobic methanotrophy was mostly sustained by the growth of type II methanotrophs in these low-pH paddy soils.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the ratios of 13 C-labeled type II to type I methanotrophs were 20.0 to 101 in the low-pH soils of YX, YT and TY (Table S4). Assuming that one cell contained two copies of pmoA genes (Kolb et al, 2003), type II methanotrophs could reach a cell-specific methane oxidation rate of 0.2-9.6 fmol CH 4 h −1 cell −1 in these three soils (calculated in Table S4), being consistent with previous report of 0.2-15 fmol CH 4 h −1 cell −1 obtained from both pure cultures and complex soils (Hanson and Hanson, 1996). These results thus suggest that aerobic methanotrophy was mostly sustained by the growth of type II methanotrophs in these low-pH paddy soils.…”
Section: Discussionsupporting
confidence: 91%
“…Despite different compositions of active methanotrophs, there was no fundamental difference of methane oxidation rate between low-pH and high-pH paddy soils, indicating similar methane oxidation rate of type II and I methanotrophs in rice paddy fields. The culture-dependent studies have showed similar kinetic traits between these two groups of methanotrophs, including substrate affinity and specific cell activity (Bedard and Knowles, 1989;Calhoun and King, 1998;Hanson and Hanson, 1996), which might explain the similar methane oxidation rates in different soils in the present study. The significant 13 C enrichment of soil organic C indicated that 13 CH 4 -derived microbial biomass contributed significantly to the turnover of soil C. Metaanalysis indicated microbial biomass represents 0.6 %-1.1 % of total soil organic C (Fierer et al, 2009), but the contri-bution of methane-driven microbial food web to soil fertility and quality remained largely unknown (Murase and Frenzel, 2007).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Through the oxidation of methane, a significant greenhouse gas, they play an important role in the global cycling of carbon. Furthermore, they play a significant role in contaminant co-metabolism [2]. Their ability to co-metabolize chlorinated ethenes is important because these compounds are persistent in soils and aquifers that have been exposed to them, for example, as a result of container leaks or inappropriate disposal practices.…”
Section: Introductionmentioning
confidence: 99%
“…Species of the genus Methylocystis are type II methanotrophs, classified, in part, by their possession of paired membranes aligned with the cell periphery, the serine pathway and predominant fatty acids with 18 carbons (Hanson & Hanson, 1996;Graham et al, 2002). Until recently, it was believed that all type II methanotrophs, including Methylocystis species, express the particulate form of methane monooxygenase (pMMO), and, with the exception of Methylocystis parvus OBBP T and the recently reported Methylocystis rosea SV97 T , all express the soluble form of methane monooxygenase (sMMO) at low copper concentrations (Stanley et al, 1983;Prior & Dalton, 1985;Choi et al, 2003;Wartiainen et al, 2006).…”
mentioning
confidence: 99%